The Status Quo Problem and the Role of Consumers Against Antimicrobial Resistance - Ancillotti, Mirko; Nilsson, Elin; Nordvall, Anna-Carin; Oljans, Emma (Frontiers in Sustainable Food Systems, 2022)
Antimicrobial resistance occurs when microorganisms survive exposure and proliferate in the presence of therapeutic levels of antimicrobial drugs. Because antimicrobial resistance is increasing, it is vital to encourage consumers to change and adopt smarter antibiotic behaviour. Despite World Health Organization’s efforts to combat antibiotic resistance and their emphasis on the importance of public involvement, the role of consumers has been overlooked. The manifold responsibility for antibiotic resistance extends across different actors, including food retailers and consumers. Given this shared responsibility, a blame game arises and no action occurs. To overcome this status quo situation, we draw attention to the potential role of individual responsibility and social pressure to encourage consumers to adopt smart antibiotic behavior but also to empower them. Conditions must be put in place to enable consumers’ critical evaluation of the health-related and ethical aspects of their food choices. Such behaviour can be facilitated using digital innovations to support informed choices, in store and online.